Students’ voices on ChatGPT: A pilot study on academic writing enhancement - Setya Ariani; Noor Rachmawaty; Puji Astuti Amalia (Journal of Research on English and Language Learning (J-REaLL), 2026)
ChatGPT is regarded as a beneficial resource for learning, as it offers feedback and support throughout the academic writing process. The current literature primarily focuses on the benefits and drawbacks of ChatGPT, with a relatively minor emphasis on the students’ actual experiences in the local higher education setting. This paper is written to explore students’ experiences, perceptions, and reflections in relation to their use of ChatGPT for improving academic writing performance. A pilot study was conducted using an online open-response questionnaire distributed to the second-semester students enrolled in the academic writing course in the English Literature Study Program. A total of thirty-two students were identified as the target group for participation; however, only fourteen were able to fully complete the questionnaire. The students responded to the questionnaire items addressing the integration of ChatGPT in academic writing, writing quality and confidence, students' beliefs and concerns about ChatGPT, as well as the difficulties they face concerning plagiarism. The findings indicated that students did not frequently use ChatGPT for writing assistance. In addition, the themes emerged from students’ responses included the development of ideas, the provision of feedback, the autonomy of writers, grammar, vocabulary, sentence construction, structuring of paragraph and essay, awareness of the limitations of ChatGPT, and the maintenance of academic integrity. Understanding students’ voices on ChatGPT can help educators in making informed decisions on the use of AI tools in academic writing instruction. A limited sample size is more susceptible to bias, and therefore future studies should involve larger samples employing a variety of research designs.